Strengthening Maternal and Child Health Services: Evaluating the KIA Book Training Program for Posyandu Cadres - Nurmilawati, Nurmilawati; Nugroho, Adi; Audhah, Nelly Al; Febriana, Silvia Kristanti Tri; Noor, Meitria Syahadatina (Universitas Tribhuwana Tunggadewi, 2024)
This study explores the effects of a comprehensive training program on the skills, knowledge, and motivation of Posyandu cadres in Guntung Manggis, Banjarbaru, Indonesia—a region with notably high maternal and infant mortality rates. The sample included 68 Posyandu cadres, divided equally into intervention and control groups. The intervention group underwent an interactive, hands-on training program, which led to significant improvements in knowledge and practical skills compared to the control group. Post-training, the intervention group’s mean skills score increased from 48.24 ± 6.47 to 74.15 ± 7.85, while the control group showed no significant change. These findings suggest that comprehensive training programs, which incorporate practical and interactive components, are more effective than traditional lecture-based methods in enhancing cadre competencies. It is recommended that health authorities consider adopting such training programs on a larger scale, particularly in high-need areas, as a strategy to improve maternal and child health outcomes and reduce maternal and infant mortality rates.